The Role of Parental Involvement in Supporting Early English Learning Among Preschool Children - Rismareni Pransiska; Sri Cahaya Sihombing (Universitas Sulawesi Barat, 2026)
This research is designed to investigate the characteristics and contribution of parental involvement toward English vocabulary readiness among preschool children in West Sumatra, Indonesia. Methods: A cross-sectional survey of 150 parents of children aged four–six years was conducted. Four domains were used to measure parental involvement: home-based learning activities, providing learning resources for children aged 0–6 years (e.g., books, games), exposure routines, and parents' self-efficacy. Descriptive statistics, Pearson correlation, and hierarchical multiple regression were conducted to analyze the data. The results showed moderate to high parental involvement, with self-efficacy being the most strongly associated with children’s English readiness. (r = .524, p < .001). Results from regression analysis indicated that parental involvement was a significant predictor of English readiness (R² = .398, p < .001), with self-efficacy (β = .312, p < .001) and home-based learning (β = .285, p < .001) as the strongest predictors. Urban families had better access to learning resources and English exposure; however, parental engagement and self-efficacy were similar across urban and rural groups. These results demonstrate that psychological factors, and uniquely parental confidence, shape early English development at least as much as material resources. The main contribution of this study is demonstrating that parental self-efficacy and home-based learning involvement are the strongest predictors of children's English readiness, suggesting that interventions targeting parental confidence and home learning practices offer an effective approach to support early English language development in EFL contexts.